2019
DOI: 10.1186/s12879-019-4332-5
|View full text |Cite
|
Sign up to set email alerts
|

Gynecomastia in HIV-positive adult men receiving efavirenz-based antiretroviral therapy at Newlands clinic, Harare, Zimbabwe

Abstract: Background Gynecomastia is known to occur in some men taking an efavirenz-based antiretroviral therapy (ART) regimen. However, the incidence and outcomes of gynecomastia are not known in Zimbabwe. We described the characteristics and outcomes of gynecomastia among male patients on an efavirenz-based ART regimen. Methods We conducted a retrospective cohort review of data of all male patients aged ≥18 years taking an efavirenz-based regimen at Newlands Clinic, Harare, Zim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In the literature, the reported cases were bilateral and resolved upon discontinuation of efavirenz, similar to our patient (Table 1) [9,10,12,13,16,17]. The time of resolution in our case report was two months after the discontinuation of efavirenz, which is comparable to other studies that have reported a resolution time of three to 10 months [9,10,12,13,16,17].…”
Section: Discussionsupporting
confidence: 89%
“…In the literature, the reported cases were bilateral and resolved upon discontinuation of efavirenz, similar to our patient (Table 1) [9,10,12,13,16,17]. The time of resolution in our case report was two months after the discontinuation of efavirenz, which is comparable to other studies that have reported a resolution time of three to 10 months [9,10,12,13,16,17].…”
Section: Discussionsupporting
confidence: 89%
“…See Online for appendix gynaecomastia 21 ) suggesting a potential role of ART on circulating sex hormone concentrations. Therefore, the difference in survival after a breast cancer diagnosis between women with and without HIV (hereafter referred to as the HIV differential) might reflect, at least in part, an ART effect that could differ according to the tumour hormone receptor status.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…Gynaecomastia is a side-effect of antiretroviral therapy. FNA and CNB will readily make this distinction as the management differs [23].…”
Section: Discussionmentioning
confidence: 99%